Awareness of human papillomavirus and acceptability of the vaccine among women in Palestine: is it time for policy adjustment? - Mohamedraed Elshami; Hanan Abukmail; Ibrahim Al-Slaibi; Mohammed Alser; Afnan Radaydeh; Alaa Alfuqaha; Mariam Thalji; Salma Khader; Lana Khatib; Nour Fannoun; Bisan Ahmad; Lina Kassab; et al. (BMC, 2022)
Abstract Background Progress has been made in the reduction of morbidity and mortality of cervical cancer by the implementation of human papillomavirus (HPV) vaccination programs. This study aimed to assess the awareness of Palestinian women about HPV as well as their knowledge and acceptability of the HPV vaccine and to examine the factors associated with good awareness. Methods This was a national cross-sectional study. Adult women were recruited from hospitals, primary healthcare centers, and public spaces in 11 Palestinian governorates using convenience sampling. A structured questionnaire was used for data collection. For each correctly answered question, one point was given. The total score was calculated and categorized into poor (0-10) and good awareness (11-21). Results The questionnaire was completed by 7223 women out of 8086 who were approached (response rate = 89.3%). A total of 7058 questionnaires were included in the final analysis; 4403 from the West Bank and Jerusalem (WBJ) and 2655 from the Gaza Strip. Women recruited from the Gaza Strip were younger, getting lower monthly incomes, and with fewer chronic diseases than women recruited from the WBJ. Only 33 women (0.5%) displayed good awareness of HPV and its vaccine with 0.7% of women from WBJ and only 0.2% of women from the Gaza Strip. Completing post-secondary education, being employed or a student, and having a higher monthly income were associated with an increase in the likelihood of having good awareness. Among women who had heard of HPV (n = 571, 8.1%), only 46 women (8.1%) reported familiarity with its vaccine. Women from the WBJ were more likely than women from the Gaza Strip to have heard about the HPV vaccine (0.9% vs. 0.2%). Most women agreed to receive the HPV vaccine themselves or for their daughters if it was given without cost or with a co-payment. No differences were found in the likelihood of agreeing to receive the HPV vaccine among women in the WBJ versus the Gaza Strip. Conclusion The overall awareness of HPV and its vaccine was extremely low. Inclusion of the HPV vaccine in the national immunization program could change this, especially as the HPV vaccine appeared to be acceptable.